Review of official responsibility for the Salish Sea marine environment. (1st October 2021) - Jones, Jacob; Keller, Peter; van der Flier Keller, Eileen
Abstract: This paper introduces official responsibility for the protection and management of the Salish Sea marine environment. Focusing on governments and their legally constituted bodies, the complex management structures on the American and Canadian sides of the Salish Sea are identified. Both countries operate in cooperative federalist systems, but there exist differences in management structures arising notably from constitutional differences, Tribal and First Nation relations, and jurisdictional authority. Both state and provincial governments have the authority to create and enforce environmental regulations but are constrained by federal legislation. Collaborative and stakeholder-engaged environmental planning and stewardship have been recognized on both sides of the border. Past and present efforts support bottom-up organizational structures that give community members and scientists a greater voice in decision-making, in partnership with government. More evidence exists of community- and state-level autonomy in Washington compared to British Columbia. Political and administrative boundaries have been recognized by some as counter to needs of environmental management, with an alternative and preferred approach being the use of ecological planning units such as watersheds or estuaries. The international boundary dividing the Salish Sea remains an administrative and organizational impediment despite evidence of trans-boundary collaborative efforts. Graphical abstract: Image 1 Highlights: Official responsibilities and management structures differ between the USA and Canada because of respective constitutions, Tribal and First Nation relations, and jurisdictional authority. . Washington State and British Columbia enforce environmental regulations but are constrained by federal legislation. . Collaborative and stakeholder-engaged environmental planning and stewardship have been recognized on both sides of the border. The international boundary remains an administrative and organizational impediment despite evidence of trans-boundary collaborative efforts.